Negative effect of cyclin D1 overexpression on recurrence-free survival in stage II-IIIA lung adenocarcinoma and its expression modulation by vorinostat in vitro. Issue 1 (December 2015) - Lee, Eunju; Jin, DongHao; Lee, Bo; Kim, Yujin; Han, Joungho; Shim, Young; Kim, Duk-Hwan
Abstract Background This study was aimed at identifying prognostic biomarkers for stage II-IIIA non-small cell lung cancer (NSCLC) according to histology and at investigating the effect of vorinostat on the expression of these biomarkers. Methods Expression levels of cyclin D1, cyclin A2, cyclin E, and p16 proteins that are involved in the G1 -to-S phase progression of cell cycle were analyzed using immunohistochemistry in formalin-fixed paraffin-embedded tissues from 372 samples of stage II-IIIA NSCLC. The effect of vorinostat on the expression of these proteins, impacts on cell cycle, and histone modification was explored in lung cancer cells. Results Abnormal expression of cyclin A2, cyclin D1, cyclin E, and p16 was found in 66, 47, 34, and 51 % of 372 cases, respectively. Amongst the four proteins, only cyclin D1 overexpression was significantly associated with poor recurrence-free survival (adjusted hazard ratio = 1.87; 95 % confidence interval = 1.12 – 2.69, P = 0.02) in adenocarcinoma but not in squamous cell carcinoma (P = 0.44). Vorinostat inhibited cell cycle progression to the S-phase and induced down-regulation of cyclin D1 in vitro. The down-regulation of cyclin D1 by vorinostat was comparable to a siRNA-mediated knockdown of cyclin D1 in A549 cells, but vorinostat in the presence of benzo[a]pyrene showed a differential effect in different lung cancer cell lines. Cyclin D1 down-regulation by vorinostat was associated with the accumulation of dimethyl-H3K9 at the promoter of the gene. Conclusions The present study suggests that cyclin D1 may be an independent prognostic factor for recurrence-free survival in stage II-IIIA adenocarcinoma of lung and its expression may be modulated by vorinostat.